A situational analysis of pharmacovigilance plans in the Global Fund Malaria and U.S. President's Malaria Initiative proposals - Stergachis, Andy (BioMed Central, 2010)
BACKGROUND: Pharmacovigilance programmes can monitor and help ensure the safe use of medicines that are critical to the success of global public health programmes. The widespread deployment of artemisinin-based combination therapy (ACT) by national malaria control programmes as part of the overall Global Malaria Action Plan for malaria control to elimination and eradication makes ACT an excellent candidate for pharmacovigilance activities. In 2008, The Roll Back Malaria partnership issued guidelines for inclusion of pharmacovigilance in Global Fund and other related proposals. In light of this recommendation and the rapid scale-up of ACT worldwide, an analysis of Global Fund Round 8 proposals and the President's Malaria Initiative (PMI) 2009 Malaria Operational Plans was conducted to assess if and how pharmacovigilance has been incorporated into countries' national malaria plans and donor budget requests. METHODS: The Global Fund - Malaria Round 8 proposals for the 26 countries and the PMI Malaria Operational Plans (MOPs) for fiscal year 2009 for the 15 countries that were approved and received funding from either the Global Fund - Malaria Round 8 or PMI were accessed through the programme websites. The analysis consisted of conducting word counts and key word in context analyses of each proposal and plan. RESULTS: Twelve out of 26 (46%) of the Global Fund proposals mentioned that established pharmacovigilance systems were present in their countries. Four of the fifteen PMI MOPs (27%) mentioned that established pharmacovigilance systems were present in their countries. Only seven of the 26 (27%) Global Fund proposals included a request for funding for new or current pharmacovigilance activities. Seven of 15 (47%) MOPs included a request for funding for pharmacovigilance activities. CONCLUSIONS: There were relatively few requests for funding for pharmacovigilance activities, demonstrating a lack of emphasis placed on pharmacovigilance systems in recipient countries. The findings stress the need for more active direction to strengthen active surveillance and passive adverse event reporting systems to augment the issuance of guidance documents.